2017
DOI: 10.1097/qai.0000000000001374
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of HIV Seroconverters in a TDF/FTC PrEP Study: HPTN 067/ADAPT

Abstract: Background HPTN 067/ADAPT evaluated tenofovir disoproxil fumarate/emtricitabine (TDF/FTC) pre-exposure prophylaxis (PrEP) in women (South Africa) and men who have sex with men (Thailand, US). Participants received once-weekly directly observed TDF/FTC (DOT), and were then randomized to daily, time-driven, or event-driven PrEP. This report describes characterization of 12 HIV seroconversion events in this trial. Methods HIV rapid testing was performed at study sites. Retrospective testing included: 4th genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
1
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 19 publications
0
35
1
2
Order By: Relevance
“…Case reports have detailed atypical HIV‐antibody test results in those taking PrEP , with the possibility of a delayed or reduced antibody response to HIV infection and suppressed viral replication. In the ADAPT trial (HIV Prevention Trials Network (HPTN) 067) that evaluated TDF/FTC PrEP in women in South Africa and men who have sex with men (MSM) in Thailand and USA, there were 12 new HIV infections . In 9 of the 12 cases, both of two POCTs were non‐reactive at the first HIV‐positive visit, including eight cases of AHI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Case reports have detailed atypical HIV‐antibody test results in those taking PrEP , with the possibility of a delayed or reduced antibody response to HIV infection and suppressed viral replication. In the ADAPT trial (HIV Prevention Trials Network (HPTN) 067) that evaluated TDF/FTC PrEP in women in South Africa and men who have sex with men (MSM) in Thailand and USA, there were 12 new HIV infections . In 9 of the 12 cases, both of two POCTs were non‐reactive at the first HIV‐positive visit, including eight cases of AHI.…”
Section: Discussionmentioning
confidence: 99%
“…The viral load was ≤ 400 copies/mL in four of the eight AHI cases, but all were positive on a sensitive HIV RNA qualitative assay. In eight cases there was continuation of PrEP, including one case where PrEP was continued for three to four months post HIV infection; there were three cases of drug resistance to ART . In an assessment of HIV diagnostic tests in the ANRS‐IPERGAY study, the Abbott Architect ® Ag/Ab Combo test detected 85% of AHI but failed to detect two early infections, both which had HIV RNA of < 500 copies/mL .…”
Section: Discussionmentioning
confidence: 99%
“…Thirteen randomized studies have investigated the efficacy and/or optimal dosing schedule of oral TDF with or without FTC as PrEP and have reported rates of antiretroviral drug resistance observed during study follow-up [3][4][5][6][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. These studies demonstrated that PrEP is safe, well tolerated and able to decrease HIV transmission in multiple priority populations.…”
Section: Hiv Drug Resistance In Randomized Clinical Trials Of Prepmentioning
confidence: 99%
“…There is general agreement that the vast majority of cases of PrEP failure are simply due to poor adherence to the drug, as evidenced by the low PrEP drug levels seen in seroconverters within the main PrEP efficacy trials (Table 2) [14,23,30]. For instance, in the iPrEx trial, a subgroup analysis among those randomized to active drug showed that 8% of those who developed HIV infection had detectable levels of study drug in either plasma or peripheral blood mononuclear cells (PBMCs), compared with 54% of individuals who did not develop infections and were considered to be 'on treatment' (taking drug on >50% of days) [6].…”
Section: Prep Failure Due To Nonadherencementioning
confidence: 99%